Burkitt's Lymphoma Involving Multiple Hormone-Producing Organs on FDG PET/CT. (December 2019) - Wen, Zhe; Zhuang, Hongming
Abstract : Abstract: Lymphoma involving many different organs can be occasionally observed. However, lymphoma involvement of multiple hormone-producing organs is rare. In this report, we described our FDG PET/CT findings in a 21-year-old man whose Burkitt's lymphoma involved not only lymph nodes, the spleen, the brain, and the bones, but also 4 organs in the endocrine system, including the thyroid, right adrenal, the pancreas, and the right testicle.